Effect of chemical modification of wood flour on properties of polypropylene-nano SiO2 hybrid nanocomposite - Saeid Ismaeilimoghadam (Regional Information Center for Science and Technology (RICeST), 2015)
This research with aim of evaluation the effect of chemical treatment of wood flour on physical, mechanical and morphological properties of polypropylene-nano SiO2 hybrid nanocomposite were done. For this purpose, wood flour with sodium hydroxide and benzyl chloride to chemically treatment. For ensure the chemical treatment, Fourier transform infrared (FTIR) spectroscopy tests was done on the treated and untreated wood flour. Wood flour at 60% weight ratio with polypropylene with 4% maleic anhydrate grafted polypropylene coupling agent in extrusion were mixed. Also Nano SiO2 with 0, 1, 3 and 5% as filler was used. The sample specimen were manufactured by using injection molding techniques. Then mechanical tests such as bending resistance and modulus and physical tests such as water absorption and thickness swelling according to the ASTM standard was done on the samples. Also for morphological investigation on the Nano composites from Scanning Electron Microscopy (SEM) was used. Results showed that the bending resistance and modulus increased with effect of chemical treatment but water absorption and thickness swelling decreased. With increase of Nano SiO2 to 3% the mechanical properties increased but adding further amount Nano particles reduced the mechanical properties. With increase of SiO2 Nano particles to 5% the water absorption in Nano composites were increased, but thickness swelling was decrease. The results of SEM showed an improvement in interface between filler and matrix with effect of chemical treatment Also transmittance of Nano SiO2 to 3% levels was good.